Numerical analysis of sodar echo signals - FORTUNA, J. (Archives of Acoustics, 1995)
The results of analysis based on the FFT with some methods of evaluating the power spectrum of sodar echo signals for investigating the vertical profiles of wind speed in lower atmosphere are discussed in the article. The best from the point of view of spreading of spectrum and computing time occurs to be the Goodman–Enochson–Otnes method (GEO) with frequency weight window. The results of applying the GEO method to evaluating the vertical profile of wind speed in lower atmosphere by means of MUT sodar are presented.